(untitled) (Feni University Journal, 2026)
This paper uses critical discourse analysis to examine Bangabandhu Sheikh Mujibur Rahman’s speech delivered on 7th March 1971. Analysing language techniques in the sociopolitical context of Bangladesh in 1971, the paper explores societal consequences, power structures, and ideological conceptions. The research examines discourse practice, textual and sociocultural elements and demonstrates how language shapes power structures, transmits ideologies, and affects social transformation. This analysis aims to contribute to the larger conversation on the role of language in political narratives and historical transformations by offering a nuanced understanding of the speech’s rhetorical significance. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (155-166)